Company law and directors' duties in Sub-Saharan Africa : fixing the enforcement regime - Akanmidu, Oludara (Routledge, 2024)
"This book provides a critical analysis of the enforcement regime for breach of directors' duties in sub-Saharan Africa. Focusing on Nigeria, Kenya, Ghana, and Tanzania, it interrogates the current 'state of play' regarding enforcement of directors' duties in sub-Saharan African countries. The book examines the effectiveness of enforcement, the reasons for its successes or failures and how it might be improved in these countries. Finally, taking into consideration the specific socio-cultural context of the countries in question, it offers persuasive and practical avenues for reform. This book will be of interest to scholars and practitioners of comparative corporate law and corporate governance in Africa"-- Provided by publisher.
Keywords: Corporation law -- Africa, Sub-Saharan.; Directors of corporations -- Legal status, laws, etc. -- Africa, Sub-Saharan.; Breach of trust -- Africa, Sub-Saharan.; elektronické knihy; electronic books